Peningkatan Keterampilan Menulis Puisi melalui Teknik Kata Kunci Berbantuan Media Foto pada Peserta Didik Kelas X SMA - Siti Wahyuni; Raden Yusuf Sidiq Budiawan; Winarni Rahayu (Jurnal Pendidikan Guru Profesional, 2024)
Learning to write poetry is one of the materials found in class X at the high school level. This research aims to improve poetry writing skills in class X students at SMA Negeri 5 Semarang through the application of keyword techniques assisted by photo media. This research uses quantitative methods with a classroom action research (PTK) design involving two cycles. Each cycle consists of planning, implementation, observation, and reflection. Data collection techniques used include observation, tests and documentation. The results of the research show that using keyword techniques assisted by photo media can improve students' poetry text writing skills. The improvement in poetry text writing skills can be seen from the test results given, where in the first cycle of activities the percentage was 27.8%, while in the second cycle the percentage increased to 94.4%. Thus, the keyword technique assisted by photo media has proven to be effective in improving poetry writing skills in class X students at SMA Negeri 5 Semarang. It is hoped that these findings can become a reference for teachers in implementing innovative methods to improve students' writing skills. The implementation of this technique also shows that the use of visual media can stimulate students' imagination, so that it is easier for them to express ideas and feelings into poetry. This research makes a positive contribution to the development of more creative and effective teaching methods in the field of literacy.